Delivery of Antioxidant and Anti-inflammatory Agents for Tissue Engineered Vascular Grafts - Washington, Kenyatta S.; Bashur, Chris A. (Frontiers in Pharmacology, 2017)
The treatment of patients with severe coronary and peripheral artery disease represents a significant clinical need, especially for those patients that require a bypass graft and do not have viable veins for autologous grafting. Tissue engineering is being investigated to generate an alternative graft. While tissue engineering requires surgical intervention, the release of pharmacological agents is also an important part of many tissue engineering strategies. Delivery of these agents offers the potential to overcome the major concerns for graft patency and viability. These concerns are related to an extended inflammatory response and its impact on vascular cells such as endothelial cells. This review discusses the drugs that have been released from vascular tissue engineering scaffolds and some of the non-traditional ways that the drugs are presented to the cells. The impact of antioxidant compounds and gasotransmitters, such as nitric oxide and carbon monoxide, are discussed in detail. The application of tissue engineering and drug delivery principles to biodegradable stents is also briefly discussed. Overall, there are scaffold-based drug delivery techniques that have shown promise for vascular tissue engineering, but much of this work is in the early stages and there are still opportunities to incorporate additional drugs to modulate the inflammatory process.